COVID-19 Infection in Men on Testosterone Replacement Therapy. Issue 1 (9th October 2020) - Rambhatla, Amarnath; Bronkema, Chandler J.; Corsi, Nicholas; Keeley, Jacob; Sood, Akshay; Affas, Ziad; Dabaja, Ali A.; Rogers, Craig G.; Liroff, Stephen A.; Abdollah, Firas
ABSTRACT: Background: Men who contract coronavirus disease 2019 (COVID-19) appear to have worse clinical outcomes compared with women which raises the possibility of androgen-dependent effects. Aim: We sought to determine if testosterone replacement therapy (TRT) is associated with worse clinical outcomes. Methods: Through a retrospective chart review, we identified 32 men diagnosed with COVID-19 and on TRT. They were propensity score matched to 63 men diagnosed with COVID-19 and not on TRT. Data regarding comorbidities and endpoints such as hospital admission, intensive care unit admission, ventilator utilization, thromboembolic events, and death were extracted. Chi-square and Kruskal-Wallis tests examined differences in categorical and continuous variables, respectively. Logistic regression analysis tested the relationship between TRT status and the study endpoints. Results: There were no statistically significant differences between the 2 groups, and TRT was not a predictor of any of the endpoints on multivariate analysis. Conclusion: These results suggest that TRT is not associated with a worse clinical outcome in men diagnosed with COVID-19.